Quality of child care influences children’s attentiveness and emotional regulation at school entry - Gialamas, A; Sawyer, M G; Mittinty, M N; Zubrick, S R; Lynch, J; Sawyer, A (My University, 2014)
Introduction: There is growing evidence that high quality child care can contribute to children’s learning, development and successful transition to school. Child care is a key caregiving setting where learning how to relate to others and regulating emotions and behaviours takes place. With significant numbers of children attending formal child care, the quality of care may be an important influence on children’s ability to attend to and persist with tasks and regulate their emotions as they start school. Methods: Using data from the Longitudinal Study of Australian Children we examined the association between the quality of formal child care at 2-3 years and children’s task attentiveness and emotional regulation at 4-5 and 6-7 years (n=1038). Three aspects of child care quality were assessed: provider and program characteristics of care; activities in childcare and the carer-child relationship. Associations between child care quality and task attentiveness and emotional regulation were investigated in linear regression analyses adjusted for confounding, with imputation for missing data. Results: There was no association between any provider or program characteristics of child care and children’s task attentiveness and emotional regulation. The quality of activities in child care were only associated with higher levels of emotional regulation at 4-5 years (β=0.24, 95% CI, 0.03-0.44) and 6-7 years (β=0.26, 95% CI, 0.04-0.48). Higher quality carer-child relationships were associated with higher levels of task attentiveness (β=0.20, 95% CI, 0.05-0.36) and emotional regulation at 4-5 years (β=0.19, 95% CI, 0.04-0.34) that persisted to 6-7 years (β=0.26, 95% CI, 0.10-0.42) (β=0.31, 95% CI, 0.16-0.47). Conclusion: Among children using formal childcare, those who experienced higher quality relationships were better able to regulate their attention and emotions as they started school. Higher emotional regulation was also observed for children engaged in more activities in childcare. Beneficial effects were stable over time.
Keywords: Children -- Early childhood; Child Care; Child Development -- Behaviour; Childhood and child development; Child Development; Children; Child Care; Early childhood; Behaviour; Childhood and child development